Pembiasaan Sholat Dhuha dalam Menumbuhkan Kedisiplinan Peserta Didik di MI Al Manar KarawanG - Riski Lestari, Ayu; Amirudin; Iqbal Amar Muzaki (Risâlah Jurnal Pendidikan dan Studi Islam, 2026)
This research aims to explore the effectiveness of the habit of Duha prayer in fosteringstudent discipline at MI Al Manar Karawang. Discipline is an important aspect that needs to beinstilled from an early age, especially in the school environment, to form good character and improvethe quality of student learning. Dhuha prayer was chosen as a routine activity because it is believed tohelp develop students' time discipline and responsibility. This research uses a qualitative method witha case study approach. Data was collected through direct observation, in-depth interviews withteachers and students, as well as analysis of documents related to the dhuha prayer habituationprogram. The participants in this research consisted of 10 teachers and 30 students at MI Al ManarKarawang. Observations were carried out for two months to see the implementation and impact ofDuha prayer activities on student discipline. In-depth interviews were conducted to exploreparticipants' views and experiences regarding this program. The results of the research show that thehabit of Duha prayer significantly increases student discipline. Students who regularly attend Dhuhaprayers show an increase in punctuality, responsibility for assignments, and regularity in dailyactivities. Teachers also reported positive changes in students' attitudes and behavior, such asincreased enthusiasm for learning and compliance with school regulations. Apart from that, providingsanctions for students who do not attend Duha prayers without clear reasons is also effective instrengthening their commitment to discipline. The conclusion of this research is that the practice ofDuha prayer at MI Al Manar Karawang has succeeded in growing student discipline significantly. Thisprogram not only helps students become more disciplined in matters of worship, but also in everydaylife, thereby improving the quality of their education and overall character. Therefore, implementingreligious activities such as Duha prayers can be an effective strategy in efforts to improve discipline inschools.